Pengembangan E-LKPD Berbasis STEM dalam Pembelajaran IPA Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SMP - Ayu Agustina Zahro; Pramudya Dwi Aristya Putra (Jurnal Pelita: Jurnal Pembelajaran IPA Terpadu, 2026)
This study aims to develop a STEM-based E-LKPD (Electronic Student Worksheet) in science learning to improve junior high school students’ critical thinking skills. The urgency of this research is driven by the low level of students' critical thinking skills and the need for digital learning media innovations that align with the Kurikulum Merdeka. This study is a Research and Development (R&D) project employing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects involved 22 eighth-grade students at SMP Negeri 2 Maesan, selected through a purposive sampling technique. Data collection instruments included expert validation sheets, observation sheets for learning implementation, pre-test and post-test based on Ennis's critical thinking indicators, and student response questionnaires. Data analysis techniques involved descriptive quantitative and qualitative methods, including the calculation of Normalized Gain (N-gain) to measure effectiveness. The results showed that the developed STEM-based E-LKPD was highly valid with a percentage of 99.31%, very practical with an average of 94.99%, and effective in improving students’ critical thinking skills. This effectiveness was evidenced by the increase in scores from a pre-test average of 31.91 to a post-test average of 86.37, with an N-gain score of 0.8 (high category). Furthermore, student responses reached 98.96%, categorized as very good. These findings indicate that the STEM-based E-LKPD is feasible and effective as a learning medium to equip students with 21st-century skills.